2004
DOI: 10.1128/cdli.11.2.266-271.2004
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of Interleukin-10 Production by Acidic β-Lactoglobulin-Derived Peptides Hydrolyzed withLactobacillus paracaseiNCC2461 Peptidases

Abstract: We have previously demonstrated that Lactobacillus paracasei NCC2461 may help to prevent cow's milk allergy in mice by inducing oral tolerance to ␤-lactoglobulin (BLG). To investigate the mechanisms involved in this beneficial effect, we examined the possibility that L. paracasei induces tolerance by hydrolyzing BLGderived peptides and liberating peptides that stimulate interleukin-10 (IL-10) production. L. paracasei peptidases have been shown to hydrolyze tryptic-chymotryptic peptides from BLG, releasing nume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
2
5

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(51 citation statements)
references
References 43 publications
0
44
2
5
Order By: Relevance
“…It was demonstrated that L. paracasei NCC2461 participates in -lactoglobulin (BLG) oral tolerance process in mice, attributable to the hydrolysis of BLG into peptides, which stimulate the production of IL-10 ( Fig. 3) [197,198]. Thus, the increased IL-10 production in turn may drive the induction of Tregs in addition to its immunosuppressive effects.…”
Section: Microbial Metabolites Generated By the Breakdown Of Foodmentioning
confidence: 99%
“…It was demonstrated that L. paracasei NCC2461 participates in -lactoglobulin (BLG) oral tolerance process in mice, attributable to the hydrolysis of BLG into peptides, which stimulate the production of IL-10 ( Fig. 3) [197,198]. Thus, the increased IL-10 production in turn may drive the induction of Tregs in addition to its immunosuppressive effects.…”
Section: Microbial Metabolites Generated By the Breakdown Of Foodmentioning
confidence: 99%
“…Cependant, en se référant à la théorie d'un défaut de régulation, il est également envisagé que des souches ayant des propriétés immunorégulatrices, notamment favorisant la production d'IL-10 et l'induction de Treg, pourraient également exercer des effets bénéfiques [28]. Des travaux récents indiquent que le mélange de probiotiques VSL#3 est capable d'exercer des effets thérapeu-tiques dans un modèle murin d'allergie alimentaire, en favorisant à la fois une repolarisation de la réponse Th2 vers un profil Th1 et Treg [40].…”
Section: Probiotiques Et Allergieunclassified
“…Lact . paracasei peptidases have been shown to hydrolyze tryptic -chymotryptic peptides from BLG, releasing numerous small peptides with immunomodulating properties (Prioult et al 2004 ).…”
Section: Immunomodulatory Peptidesmentioning
confidence: 99%